Faktor-Faktor yang Berhubungan dengan Kejadian Bayi Berat Lahir Rendah (BBLR) di Rumah Sakit Muhammadiyah Palembang Tahun 2020 - Idha Budiarti; Rohaya Rohaya; Titin Dewi Sartika Silaban (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Low birth weight baby is new born babies with weight < 2500 grams. The causative factors are chronic energy deficiency, anemia, preeclampsia, premature rupture of membranes, parity, birth spacing, gestational age, maternal age, maternal bad habits, and fetal factors. The purpose of this research is to know the relationship between parity, gestational age, hemoglobin level, and preeclampsia with the incidence of low birth weight babies in Muhammadiyah Hospital Palembang 2020. The method used in this study was analytic survey with cross sectional approach. Sample size was determined based on the Slovin formula where the respondent was 96 maternity women in Muhammadiyah Hospital Palembang 2020. The sample got using non random sampling technique which was purposive sampling by setting inclusion and exclusion criteria. The univariate analysis showed that more than half of the respondents which was 61 (63,5%) experienced low birth weight babies, respondents with parity risk category was 49 (51,0%), respondents with pregnancy is not risk was 67 (69,8%), respondents with hemoglobin level anemia was 63 (65,6%), and 48 respondents (50%) was preeclampsia. The chi-square statistical test showed that there was significant relationship between parity, gestational age, hemoglobin level, and preeclampsia with the incidence of low birth weight babies with p value (0.007, 0.000, 0.015, and 0.000). The conclusion of this research is there was significant relationship between parity, gestational age, hemoglobin level, and preeclampsia with the incidence of low birth weight babies in Muhammadiyah Hospital Palembang 2020. This research is hope to be useful references and information to increase knowledge about the incidence of low birth weight babies, so that future research can reveal more factors related to the incidence of low birth weight babies.